Simulation and Implementation of Quasi-Z-Source Based Single-stage Buck/boost Inverter Fed Induction Motor - P. Shunmugakani; D. Kirubakaran (Institute of Advanced Engineering and Science, 2016)
Renewable power systems as distributed generation units often experience big changes in the inverter input voltage due to fluctuations of energy resources. Z-source inverter (ZSI) is known as a single-stage buck/boost inverter. The ZSI achieves voltage buck/boost in single stage, without additional switches. Triggering on state enables energy to be stored in inductors, which is released when at non-shoot-through state, followed by the voltage boost feature. The voltage-fed Z-source inverter/quasi-Z-source inverter (QZSI) has been presented suitable for photovoltaic (PV) applications mainly because of its single-stage buck and boost capability and the improved reliability.